2020
DOI: 10.1088/2631-7990/ab9ead
|View full text |Cite
|
Sign up to set email alerts
|

A review on microstructures and properties of high entropy alloys manufactured by selective laser melting

Abstract: High entropy alloys (HEAs) with multi-component solid solution microstructures have the potential for large-scale industrial applications due to their excellent mechanical and functional properties. However, the mechanical properties of HEAs limit the selection of processing technologies. Additive manufacturing technology possesses strong processing adaptability, making itthe best candidate method to overcome this issue. This comprehensive review examines the current state of selective laser melting (SLM) of H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(28 citation statements)
references
References 121 publications
0
28
0
Order By: Relevance
“…29 The higher residual stress increases the dislocation density in walls built with bidirectional strategy, which increases the material hardness. 30 However, it is observed that the micro-hardness of the wall structures built with both the strategies is lower than the micro-hardness of LDED built bulk structures at the same process parameters 22 as presented in Figure 12. This is largely due to relatively lower cooling rates in wall structures as compared to bulk structures.…”
Section: Mechanical Characterizationsmentioning
confidence: 91%
“…29 The higher residual stress increases the dislocation density in walls built with bidirectional strategy, which increases the material hardness. 30 However, it is observed that the micro-hardness of the wall structures built with both the strategies is lower than the micro-hardness of LDED built bulk structures at the same process parameters 22 as presented in Figure 12. This is largely due to relatively lower cooling rates in wall structures as compared to bulk structures.…”
Section: Mechanical Characterizationsmentioning
confidence: 91%
“…Recently, many HEA systems have been exploited, and most research focused on the microstructure and properties of the AlxCoCrFeNi HEAs system [20][21][22]. The addition of copper (Cu) to a HEA matrix has been widely investigated [23]; this is probably because the atomic radii of elements are close to one another and because there is a tendency to form a reliable solution according to the phase rule and phase diagram between them [24].…”
Section: Introductionmentioning
confidence: 99%
“…High entropy alloys (HEAs) are classically defined as the multi-principal element alloys (MPEAs) formed by mixing equal or near-equal amounts of five or more elements, and they have been ascribed to possess four major characteristics, namely, high-entropy effect, sluggish diffusion effect, severe lattice distortion effect and cocktail effect [1][2][3][4] . On the other hand, the alloys consisting of three or four principal (base) elements in equal or near-equal atomic compositions are defined as medium entropy alloys (MEAs) [5].…”
Section: Introductionmentioning
confidence: 99%